On the role of usage in the concept of the Polish standard language in the beginning of the 21st century - Kołodziejek, Ewa (Papers in Linguistics, 2023)
The article is part of the discussion on the shape of the new linguistic norm. The author characterises the contemporary linguistic reality in the context of cultural and technological changes and the resulting needs of language users. Following the example of other researchers, she postulates the adoption of the linguistic usage as the basis of the linguistic norm. Based on the use of adverbial participles and other widespread linguistic forms, the author shows the discrepancy between common linguistic custom and the rules of the codified norm.